Dynamics among nations the evolution of legitimacy and development in modern states - Root, Hilton L. (Cambridge The Mit Press, 2013)
Liberal internationalism has been the West's foreign policy agenda since the Cold War, and the West has long occupied the top rung of a hierarchical system. In this book, Hilton Root argues that international relations, like other complex ecosystems, exists in a constantly shifting landscape, in which hierarchical structures are giving way to systems of networked interdependence, changing every facet of global interaction. Accordingly, policymakers will need a new way to understand the process of change. Root suggests that the science of complex systems offers an analytical framework to explain the unforeseen development failures, governance trends, and alliance shifts in today's global political economy.
Includes bibliographical references and index.
Keywords: International economic relations